Development and validation of the NDDI‐E‐Y: a screening tool for depressive symptoms in pediatric epilepsy. (29th June 2016) - Wagner, Janelle L.; Kellermann, Tanja; Mueller, Martina; Smith, Gigi; Brooks, Byron; Arnett, Alex; Modi, Avani C.
Summary: Objectives: To validate the revised 12‐item revised Neurological Disorders Depression Inventory‐Epilepsy for Youth (NDDI‐E‐Y), a self‐report screening tool for depressive symptoms tailored to youth ages 12–17 with epilepsy. Methods: Youth at two sites completed the NDDI‐E‐Y during a routine epilepsy visit. Youth at one site also completed the Children's Depression Inventory‐2 (CDI‐2). Seizure and demographic data were abstracted from the electronic medical record. Exploratory factor analyses were conducted. Internal consistency, area under the curve (AUC), and construct validity were assessed. Results: NDDI‐E‐Y questionnaires were analyzed for 143 youth. The coefficient for internal consistency for the NDDI‐E‐Y was 0.92. Factor analyses suggested a one‐factor solution with all 12 items loading on the factor. The NDDI‐E‐Y was positively correlated with the CDI‐2 (N = 99). Sensitivity and specificity of the NDDI‐E‐Y were high. Significance: Reliability and construct validity were established for the revised 12‐item NDDI‐E‐Y. The NDDI‐E‐Y is a brief, free measure of depressive symptoms that can be administered during a routine epilepsy visit.